Development of the Emotional Wellbeing at Work Virtual Programme to support UK health visiting teams. (2nd December 2020) - Baldwin, Sharin; Stephen, Rachel; Bishop, Philippa; Kelly, Patricia
Abstract : The Covid-19 pandemic has changed the way in which health visiting services are delivered in the UK. Health visitors are now having to work more remotely, with virtual methods for service delivery as well as using personal protective equipment where face-to-face contacts are necessary. This rapid change has resulted in many health visiting staff working under greater levels of pressure, feeling isolated, anxious and unsettled. This article discusses a virtual programme that has been funded by the RCN Foundation and developed by the Institute of Health Visiting to support the emotional wellbeing of health visiting teams in the UK. It outlines the background to the project, the theoretical underpinnings to inform the programme model and the evaluation process that will be used to further refine the programme before wider implementation.